Tax Haven Use, the Pricing of Audit and Non-Audit Services, Suspicious Matters Reporting Obligations and Whistle Blower Hotline Facilities: Evidence from Australian Financial Corporations - Eulaiwi, Baban; Al-Hadi, Al-Hadi Ahmed; Taylor, Grantley; Dutta, Saurav; Duong, Lien; Richardson, Grant (Elsevier, 2021)
This study examines whether tax haven use by Australian financial corporations is associated with the pricing of audit and non-audit services. It also analyzes whether the existence of financial corporations’ suspicious matters reports (SMRs) and whistle blower hotline facilities moderate the association between tax haven use and pricing of audit and non-audit services. We find a positive association between tax haven use and the pricing of audit and non-audit services. Our results are economically significant. For example, audit fees for financial corporations with tax haven use is around 23 per cent higher compared to corporations with no tax haven use, while non-audit fees for financial corporations with tax haven use is around 13 per cent higher compared to corporations with no tax haven use. We also find that the existence of SMRs and whistle blower hotline facilities both moderate the positive association between tax haven use and audit pricing. Overall, our results suggest that tax haven use has serious consequences for financial corporations’ pricing of audit and non-audit services, whereas SMRs and whistle blower hotline facilities assist corporations to reduce the risks concerning tax haven use.